In vitro fermentation performance of alfalfa (Medicago sativa L.) mixed with different proportions of paper mulberry (Broussonetia papyrifera) leaves (PML) or condensed tannins extracted from PML - Daojie Li; Gangqin Shu; Hui Wang; Yuan Xu; Jannati Adni; Yunhua Zhang; Jennifer W. MacAdam; Juan J. Villalba; Xin Dai; Lijuan Chen (Italian Journal of Animal Science, 2021)
Ruminants would suffer from gastric distension (bloat) when feeding on alfalfa (Medicago sativa L.; Alf), while tannins can relieve this problem. Thus, this study aimed to evaluate the effect of Alf mixed with paper mulberry (Broussonetia papyrifera) leaves (PML) or condensed tannins (CT) extracted from PML on in vitro fermentation performance. Seven experimental treatments based on the mass ratios of Alf and PML were set up: Alf, PML, 3A1P (Alf:PML = 3:1), 1A1P (Alf:PML = 1:1), 1A3P (Alf:PML = 1:3), A1P (Alf with 1% CT extracted from PML), A2P (Alf with 2% CT extracted from PML), and a blank. The results after fermentation were as follows. (1) The degradable dry matter (DDM) and degradable organic matter (DOM) contents increased simultaneously with the increase in the proportion of PML (p < .05). However, the DDM and DOM contents decreased with the increase in PML CT concentration. Moreover, mixing PML with ALF improved (p <.05) the concentrations of acetic (except in 3A1P, p > .05), propionic, and butyric acids compared to Alf alone. Adding CT improved the concentrations of propionic and butyric acids over the Alf treatment (p < .05). (2) The 1A1P, 1A3P, and PML treatments showed the maximum rate of gas production during fermentation when compared with the other treatments (p < .05). The asymptotic gas volumes of the treatments with added CT were less than the Alf treatment (p < .05). It can be concluded that a mixture of Alf and PML after in vitro fermentation for 96 h could improve the DDM and DOM contents, reduce gas production, and produce more short-chain fatty acids.Highlights Adding paper mulberry leaves to Alfalfa could improve the degradable dry matter and degradable organic matter. Adding paper mulberry leaves to Alfalfa could reduce gas production, and produce more short-chain fatty acids than Alfalfa. Adding condensed tannin extracted from paper mulberry leaves to Alfalfa could reduce gas production and the maximum rate of substrate digestion, thereby preventing bloat.